An Empirical Profile of Future Work Self-Salience Among Senior High School Students in Makassar: Implications for Digital Career Guidance - Alfikriah Syahira; Muslihati; Zamroni (Prophetic : Professional, Empathy, Islamic Counseling Journal, 2026)
Technological advances, automation, and artificial intelligence have made the future of work increasingly dynamic and unpredictable, requiring students to develop career readiness beyond choosing a major, including the ability to envision and direct themselves toward a desired future work self. This urgency is salient in Indonesia given the persistently high unemployment rate among senior secondary and vocational graduates, while research on Future Work Self-Salience (FWSS), a salient representation of oneself in future work, has mostly focused on university students and employees rather than senior high school students, who are at a critical stage of career identity formation. This study aimed to describe the level of FWSS among eleventh-grade students in Makassar City, analyze gender differences, and outline its practical application for adaptive, contextual career guidance and counseling services. A quantitative cross-sectional survey was conducted with 160 students (80 male, 80 female) from 11 senior high schools, measured using the FWSS Scale and analyzed using descriptive statistics and the Mann-Whitney U test. Results showed that students FWSS generally fell into the moderate category (73.75%; M = 14.09; range 5-20), with work-identity clarity developing more strongly than job-type clarity, and a significant gender difference was found (U = 4024; p = .005; r_rb = .258), with male students scoring higher. The study concludes that senior high school students in Makassar City have begun forming a future work orientation but still require systematic, gender-sensitive support, positioning the FWSS profile as an empirical basis for developing needs-based, digitally oriented career guidance and counseling services.